EFEITO DE DIFERENTES MANEJOS CULTURAIS SOBRE A DIVERSIDADE E POPULAÇÃO DA MACROFAUNA DO SOLO - BOLES , JONAS; GALIOTTO , RODRIGO; ABRAVANEL CARVALHO , EVERTON; MAGNO BORGES DIAS , CARLOS; JOSÉ MANJABOSCO , GUSTAVO (Salão do Conhecimento, 2021)
SOLOS